2019
DOI: 10.4314/ajcem.v20i3.4
|View full text |Cite
|
Sign up to set email alerts
|

The risk of transfusion transmitted malaria and the need for malaria screening of blood donors in Abuja, Nigeria

Abstract: Background: Blood transfusion saves life but it is also a major risk factor in the transmission of certain infections such as malaria, which remains a public health problem in tropical and sub-Saharan Africa. Methodology: This study investigated the prevalence of malaria among 550 blood donors aged 18 to 60 years from blood bank units of some selected hospitals in Federal Capital Territory (FCT), Abuja, using gold standard microscopy for malaria parasite detection. Results: Two hundred and fifty two (45.8%) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Several studies conducted in Ethiopia (4.1%) [ 51 ] and Tanzania (8%) [ 52 ] reported high levels of anti-malarial antibodies. Ezeonu et al [ 53 ] in Abuja, Nigeria, recorded a higher prevalence (45.8%), whereas a lower prevalence (0.11%) was observed in Pakistan [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in Ethiopia (4.1%) [ 51 ] and Tanzania (8%) [ 52 ] reported high levels of anti-malarial antibodies. Ezeonu et al [ 53 ] in Abuja, Nigeria, recorded a higher prevalence (45.8%), whereas a lower prevalence (0.11%) was observed in Pakistan [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the STROBE criteria, two-thirds of studies (75%) were of moderate quality [22,24,[26][27][28][29][30][31][33][34][35][36][38][39][40][41]43,[45][46][47][48]50,[52][53][54][55]. Meanwhile, eight studies were of high quality (22.2%) [23,25,31,37,42,44,51,56], and one was of low quality (2.78%) [49] (Table S3).…”
Section: Reporting Quality Of the Included Studies And Qualitative Sy...mentioning
confidence: 99%
“…The remaining seven studies reported a higher proportion of malaria in Rh+ individuals than in Rh− individuals, though no statistical significance or statistical analysis has been performed [21,32,38,43,50,53,54]. Sixteen studies (44.4%) showed a lower proportion of malaria in Rh+ individuals than in Rh− individuals [23,24,26,[29][30][31]34,37,39,40,44,45,47,48,52,55]. Among these studies, a significantly lower proportion of malaria among Rh+ individuals was reported by two studies [39,44].…”
Section: Reporting Quality Of the Included Studies And Qualitative Sy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Five mosquito transmissible Plasmodium species: P. falciparum, P. vivax, P. malariae, P. ovale, and P. knowlesi, have been associated with human infections, with the first two being the most important species (25). SCD patients in tropical countries are at double risk of acquiring malaria through mosquito bites and blood transfusions because a significant proportion of tropical blood donors have asymptomatic malaria (27,28). Interestingly, a recent study demonstrated that in comparison to blood donors with SCT, donors with HbAA were associated with higher risk of asymptomatic malarial parasitaemia, which implied that HbAA blood carries higher risk of transfusion transmitted malaria (TTM) (29,30).…”
Section: Malaria and Hyperhaemolysis In Scdmentioning
confidence: 99%